Intergenerational elasticities of housing consumption and income - Lancelot Henry de Frahan; Jung Sakong (Federal Reserve Bank of Chicago, 2024)
We estimate intergenerational elasticities (IGE) of housing consumption and income in the US. Using surnames to link 1940 and 2015, we estimate a one-generation housing-consumption IGE of 0.73, higher than that of income at 0.52. Housing consumption IGE is higher for White compared to Black Americans and higher in the Northeast, patterns that contrast with income IGE. Inverting Engel curves suggests a total-consumption IGE of 0.72. Complementary to income IGE, consumption mobility is a closer measure of welfare mobility, and comparisons with income IGE inform intergenerational consumption insurance.
Keywords: J62; N32; 330; Intergenerational elasticity; Consumption mobility